International Capital Flows, External Assets, and Output Volatility - Michael Krause; Mathias Hoffmann; Peter Tillmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper proposes a new perspective on international capital flows and countries' long-run external asset position. Cross-sectional evidence for 84 developing countries shows that over the last three decades countries that have had on average higher volatility of output growth: (1) accumulated higher external assets in the long-run and (2) experienced more procyclical capital outflows over the business cycle than those countries with a same growth rate but a more stable output path. We explain this finding with a stochastic real business cycle growth model in which higher uncertainty of expected income increases households' precautionary savings. In the model, the combination of income risk and the precautionary savings motive leads to procyclical capital outflows at business cycle frequency and a higher long-run external asset position.
Keywords: F32; D83; F44; 330